ANALISIS KINERJA KEUANGAN DESA POLENGA KEC. WATUBANGGA KAB. KOLAKA TAHUN 2021-2023 - Agustina L; La Ode Turi; Surianto Surianto (Komunitas Manajemen Kompetitif, 2026)
This investigation is designed to assess the financial status of Desa Polenga, Watubangga District, Kolaka Regency in 2021–2023. This research uses a quantitative descriptive method with a village financial ratio analysis approach which includes the independence ratio, effectiveness ratio, and efficiency ratio. The data used are the realization reports of the Village Revenue and Expenditure Budget (APBDes) for 2021–2023. The results of the study show that the financial independence ratio of Desa Polenga increased every year, but it is still in the low to moderate category, which means that the village still has a fairly high dependence on transfer funds from the central and regional governments. The effectiveness ratio shows a fairly effective to effective category, which means that the village government is able to realize revenue in accordance with the targets that have been set. Meanwhile, the efficiency ratio shows a value close to 100% and fluctuates, which indicates that the use of the budget is relatively high compared to the revenue received, and in 2022 a budget deficit occurred. Overall, the financial performance of Desa Polenga shows fairly good progress, especially in terms of effectiveness and increasing independence, but efforts are still needed to improve efficiency and optimize Village Original Revenue in order to reduce dependence on transfer funds.